Indian public-sector trade unionism in an autocratic political climate: The distinctive case of Gujarat. (October 2014) - Beale, David; Noronha, Ernesto
The power and influence of trade unionism in telecommunications, state government employment and municipal bus services are examined in Gujarat, an Indian state ruled by the Hindu nationalist, pro-big business Bharatiya Janata Party. We identify significant examples of resilience in unions critical of the BJP, alongside conflicts of interest and challenges for pro-BJP unions. These are somewhat surprising findings in a context expected to be hostile to class-based trade unionism, suggesting an important pole of ongoing, organised labour opposition to Gujarat's perceived political hegemony, and posing some wider issues. In the interim between the writing and publishing of this article, the BJP won India's 2014 general election.